Neospora caninum: Activity of cholinesterases during the acute and chronic phases of an experimental infection in gerbils - Tonin A.A. (2013)
Neospora caninum causes an important immune response (cellular and humoral) in animals that it infects. Since the participation of the cholinergic system in the immune response is well documented, the aim of this study was to evaluate the relationship between N. caninum infection and activities of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) during the acute and chronic phase of infection. For that, tachyzoites of N. caninum (Nc-1 strain) were inoculated intraperitoneally in gerbils (Meriones unguiculatus), which were separated in two experiments, I and II, differing in infective doses of tachyzoites, aiming to reach an acute phase as well as chronic phase, respectively. Samples were collected on day 7 post infection (PI) for Experiment I and on days 15 and 30 PI for Experiment II. AChE activity was evaluated on whole blood and brain, while BChE was evaluated in plasma. On day 7 a reduction of AChE in total blood and brain was observed, along with reduction of BChE in plasma of infected animals when compared with non-infected. In Experiment II, AChE activity increased in total blood on day 30 PI; however, maintaining, during the same period, the AChE activity has a reduced in brain tissue. BChE activity was significantly increased on day 30 PI. Based on the results obtained, it was possible to observe a response of the cholinergic system, providing different grades of AChE and BChE activities, in response to the acute and chronic infection of gerbils experimentally infected with N. caninum. These results will serve as initial points to further studies of our research group about the relationship between the infection/disease and the cholinergic system. © 2013 Elsevier Inc.